ASUHAN KEPERAWATAN PADA PASIEN FRAKTUR EKSTREMITAS MELALUI PENERAPAN ROM PASIF DALAM MENINGKATKAN FUNGSI MOBILITAS - Elsha Estetica Senora Br Tambunan; Yovita Dwi S (Forind Press, 2026)
Extremity fractures can lead to impaired mobility, pain, and complications due to immobilization. Passive Range of Motion exercise is an essential nursing intervention to maintain joint function and prevent complications. This study aimed to describe the implementation of nursing care through passive Range of Motion in patients with femur fracture and distal fracture. The method used was a qualitative case study involving two patients hospitalized in a surgical unit with a two-day observation period. Data were collected through assessment, clinical observation, and evaluation of muscle strength, joint range of motion, pain level, and patient independence. The results showed that there was no significant improvement in mobility within two days; however, pain remained tolerable and no complications such as circulatory impairment or joint stiffness were observed. Passive Range of Motion provided preventive benefits by maintaining joint flexibility and peripheral circulation. In conclusion, this intervention is effective in preventing complications during the early phase of fracture, although it does not significantly improve mobility in a short period.